2010
DOI: 10.1186/1472-6920-10-9
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical strategies used in clinical medical education: an observational study

Abstract: BackgroundClinical teaching is a complex learning situation influenced by the learning content, the setting and the participants' actions and interactions. Few empirical studies have been conducted in order to explore how clinical supervision is carried out in authentic situations. In this study we explore how clinical teaching is carried out in a clinical environment with medical students.MethodsFollowing an ethnographic approach looking for meaning patterns, similarities and differences in how clinical teach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(81 citation statements)
references
References 21 publications
2
78
0
1
Order By: Relevance
“…Students often feel that their role within the health system is undervalued at best, and merely tolerated at worst, when in fact they have the potential to play an important role (Nilsson et al 2010). Their development as clinicians relies in part not only on their understanding of their role within the multi-disciplinary team but also in terms of the value that they perceive they bring to it.…”
Section: E471mentioning
confidence: 99%
“…Students often feel that their role within the health system is undervalued at best, and merely tolerated at worst, when in fact they have the potential to play an important role (Nilsson et al 2010). Their development as clinicians relies in part not only on their understanding of their role within the multi-disciplinary team but also in terms of the value that they perceive they bring to it.…”
Section: E471mentioning
confidence: 99%
“…Nevertheless, the teaching role is a complex one as it involves being an information provider, role model, facilitator, assessor, planner, as well as a resource developer (Harden and Crosby 2000). Clinical supervision is a central and similarly complex task for many medical teachers (Nilsson et al 2010;Taylor et al 2007). This type of teaching is characterised by the fact that it is often unplanned or opportunistic due to the unpredictable nature of medical cases.…”
Section: Introductionmentioning
confidence: 99%
“…The teacher's approach may also be related to students' approaches to learning as a teachercentred teaching approach has been associated with reproduction and a surface approach to learning whilst a student-centred teaching approach may instead support understanding and meaning making and thereby better learning outcomes (Kember 1997;Martin et al 2000;Trigwell et al 1999). Going back to clinical supervision Nilsson et al (2010) explored how this was carried out in authentic situations and identified seven pedagogical strategies. These strategies were linked to ways of understanding teaching and learning as student-or teacher-focused and each of these teaching perspectives bear consequences on the teacher's focus in clinical teaching (Nilsson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os problemas relatados, o de maior interesse para este trabalho é o da capacitação profissional, mais especificamente o aspecto pedagógico dessa prática, elemento de altíssima relevância quando se pensam os objetivos da preceptoria e sua qualidade, tal como afirmam diversos estudos (Botti & Rego, 2008Missaka & Ribeiro, 2011;Nilsson, Pennbrant, Pilhammar, & Wenestam, 2010;Paton, 2010;Smedley, 2008;Trajman, Assunção, Venturi, Tobias, Toschi, & Brant, 2009). …”
Section: A Prática Da Preceptoria Em Saúdeunclassified